Quality of shrimp analogue product as affected by addition of modified potato starch - Remya, S. (J Food Sci Technol, 2014)
The present study was aimed to investigate the effects of addition of modified potato starch on the biochemical and textural properties of shrimp analogue/imitation shrimp, a popular value-added product prepared from surimi. Three batches of shrimp analogues were prepared with 0 % (NPS), 50 % (CPS) and 100 % (MPS) of modified starch incorporation and various quality attributes were monitored at regular intervals during frozen storage (−20 °C). Loss of myofibrillar protein was least for the shrimp analogue sample added with 100 % modified potato starch. The expressible moisture content of MPS (2.48 %) was less affected by long term storage compared to CPS (3.38 %) and NPS (3.99 %). During extended low temperature storage, the textural quality of sea food analogue was highly influenced by the type of starch added to it. The percentage of modified potato starch added to shrimp analogue significantly (p ≤ 0.05) affected its hardness and fracturability. MPS samples did not show significant changes in hardness during storage as compared to other two samples. Springiness of shrimp analogue increased 2.57, 1.5 and 1.77 times with the storage period for samples with NPS, CPS and MPS, respectively. Addition of modified potato starch improved the sensory quality and textural properties of shrimp analogue and reduced the quality degradation during frozen storage as compared to NPS which contained only native potato starch.